Determining the equilibrium structures of nanoalloys by computational methods - Ferrando, Riccardo (Journal of nanoparticle research : an interdisciplinary forum for nanoscale science and technology, 2018)
Nanoalloys are bi- or multi-metallic nanoparticles with sizes in the range between 1 and 100 nm. They are the subject of intense research activity in the last decades, both in experiments and in theory/modelling. From a theoretical point of view, determining the equilibrium structure of nanoalloys at different temperatures is a quite complex task, which has stimulated the developments of specifically tailored methods and algorithms. Here, we review some recent developments in this field, considering first methods for the global optimization of nanoalloys, and then methods for studying their finite-temperature equilibrium properties.